The role of information technology in pharmaceutical supply chains - Kochman, L.; Issa, Tomayess; Alexander, Paul (IADIS press, 2010)
This research examines IT in pharmaceutical supply chains from an Australian perspective, particularly to see if benefits can be aligned with previously developed general functional IT roles as summarised in previously existing frameworks. The research focuses on pharmaceutical distribution businesses, themselves key parts of the health care supply chain. The research attempts to analyse and evaluate how IT impacts these supply chains, and in what way the use of IT improves or impacts the supply chain and supply chain management. The research also relates the findings to a framework of functional roles that IT facilitates in supply chain management (SCM). In a study by Auramo et al. (2005), three functional roles of IT in SCM were implied and included transaction execution, collaboration and co-ordination and decision making, and similar roles are examined. This study confirms the existence of similar roles though difference in relationships and emphasis of these roles is observed.